Starring Sally J. Freedman as herself - Blume, Judy. (New York : Dell Yearling, 1991)
While spending the winter of 1947-1948 in Miami Beach with her family, ten year-old Sally makes up stories, casts herself in starring roles in movies, and encounters a sinister stranger.
"A Dell Yearling book.".
Booklist.
New York Times.
School Library Journal.
5.2
5-8
Keywords: Family life -- Fiction; Historical fiction; Family life -- Fiction; Historical fiction